Continuous transformation of chiral pharmaceuticals in enzymatic membrane bioreactors for advanced wastewater treatment - Nguyen, Luong N (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
This study demonstrates continuous enantiomeric inversion and further biotransformation of chiral profens including ibuprofen, naproxen and ketoprofen by an enzymatic membrane bioreactor (EMBR) dosed with laccase. The EMBR showed non-enantioselective transformations, with high and consistent transformation of both (R)- and (S)-ibuprofen (93 ± 6%, n = 10), but lower removals of both enantiomers of naproxen (46 ± 16%, n = 10) and ketoprofen (48 ± 17%, n = 10). Enantiomeric analysis revealed a bidirectional but uneven inversion of the profens, for example 14% inversion of (R)- to (S)- compared to 4% from (S)- to (R)-naproxen. With redox-mediator addition, the enzymatic chiral inversion of both (R)- and (S)-profens remained unchanged, although the overall conversion became enantioselective; except for (S)-naproxen, the addition of redox mediator promoted the degradation of (R)-profens only